Retrospective Study of the Treatment of Infantile Hemangiomas Using a Combination of Propranolol and Pulsed Dye Laser. Issue 6 (4th March 2013) - Reddy, Kavitha K.; Blei, Francine; Brauer, Jeremy A.; Waner, Milton; Anolik, Robert; Bernstein, Leonard; Brightman, Lori; Hale, Elizabeth; Karen, Julie; Weiss, Elliot; Geronemus, Roy G.
<x xml:space="preserve">Abstract</x> Background Infantile hemangioma (IH) clearance may be slow or incomplete in response to pulsed dye laser (PDL) or propranolol alone. Objectives To evaluate whether IH treated with PDL and propranolol displayed more rapid and complete clearance than IH treated with propranolol alone. Materials and Methods Retrospective review of facial‐segmental IH treated with propranolol and PDL and controls treated with propranolol was conducted. Blinded physicians used patient photographs to select clearance level and the earliest date of near‐complete clearance. Days of propranolol, PDL sessions, and propranolol dose, each until date of near‐complete clearance; total days of propranolol; and total propranolol dose were recorded. Results Infantile hemangiomas treated concurrently with propranolol and PDL achieved complete clearance (6/12) more often than IH treated with propranolol followed by PDL (2/5) or IH treated with propranolol alone (1/8; difference in clearance scores p = .01) and achieved near‐complete clearance after fewer days of propranolol (mean 92 days for concurrent propranolol and PDL vs 288 days for propranolol; p < .001). Cumulative propranolol dose until near‐complete clearance was lowest in the concurrent propranolol and PDL group (149.16 vs 401.25 mg/kg for propranolol; p < .001). Conclusion Facial‐segmental IH treated with propranolol and PDL displayed morerapid and complete clearance and required a lower cumulative propranolol dose to achieve near‐complete clearance.